Socio-economic inequality as a problem of civic participation ("Journal "U". Economy. Management. Finance.", 2023)
Based on source materials: various articles, scientific manuals, and also referring to the work of T. Marshall "Citizenship and Social Class" was a study of the issue of socio-economic inequality as a problem of civic participation. This article aims to consider the issue of "social inequality" and its impact on life in society, in particular, special attention is paid to the issue of the relationship between inequality and civic participation.
Keywords: social inequality; citizenship; political rights; freedom; social class; civil status; poverty